2023
DOI: 10.1155/2023/4222511
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Serological Diagnosis of Typical Cat Scratch Disease and Recommendations for the Diagnostic Procedure

Abstract: Introduction. Cat scratch disease (CSD) is the most common cause of bacterial infectious lymphadenopathy, especially in children, but its diagnosis still remains challenging. Serological assays are widely applied due to their simplicity and the non-invasive sampling. However, these techniques present several limitations, including not well-defined antigen preparation, assay conditions and cutoff titers, severe cross-reactions with other species and organisms, and the notably ranging seroprevalence in the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Each of these diagnostic modalities has substantial limitations, leading to a major hurdle in the timely diagnosis and treatment of Bartonellosis [ 2 ]. A comprehensive review of studies describing serologic assays for Bartonella found that the use of these assays led to an underdiagnosis of Bartonella infection [ 7 ]. A significant fraction of patients with persistent Bartonella infection will have no detectable antibodies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these diagnostic modalities has substantial limitations, leading to a major hurdle in the timely diagnosis and treatment of Bartonellosis [ 2 ]. A comprehensive review of studies describing serologic assays for Bartonella found that the use of these assays led to an underdiagnosis of Bartonella infection [ 7 ]. A significant fraction of patients with persistent Bartonella infection will have no detectable antibodies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%